Perceptions of Technology in Language Teaching among English Pre-service Teachers - Yuvita Yuvita; Rudi Hartono; Sri Wuli Fitriati; Mursid Saleh (Universitas Negeri Semarang, 2022)
Teachers who engage in information, media, and technology must be critical thinkers with a broad perspective in order to prepare their students for the literacy demands of the twenty-first century. Language teachers' roles are crucial in developing students' literacies so that they can adapt to digital technologies in education. We've been teaching pre-service teachers about media literacy and educational technology in a variety of subject areas, as well as assisting them in incorporating new media and technologies into their curriculum design. The purpose of this study is to assess the level of digital literacy of pre-service teachers at Universitas Pancasakti Tegal and to investigate their perceptions of technology in language teaching. This study used a mixed method research design to investigate how pre-service teachers use digital technologies in the teaching and learning process during the practice of teaching in the Micro Teaching class. Furthermore, by investigating digital technologies in language teaching, pre-service teachers' perceptions are revealed. The research involved 40 pre-service teachers who are tested using Ferrari's model of digital competence areas such as information, communication, content creation, safety, and problem solving. The findings for qualitative data collection were based on classroom observation, interviews, and surveys. The findings reveal that higher levels of digital literacy in pre-service teachers influence their performance in integrating technology into their teaching process, and they are assured in motivting students to increase digital literacy skills. Their positive attitudes toward using technology in language teaching raise awareness of the importance of digital literacies and digitally literate people in developing digital literacy skills for survival in the digital age.